Ação comunicativa como base para o desenvolvimento da qualidade de vida no trabalho - Pinto, Lauisa Barbosa (2017)
This research sought to analyze the dialogical negotiation process between UFLA and SindUFLA in light of the communicative action aimed at developing Quality of Working Life (QWL). The studied context corresponds to the dialogical negotiation process occu rred during the strike period of 2015, which culminated in the signature of the “Term of agreement resulting from the negotiations between the Rectory of UFLA and S ind-UFLA, conducted during strike period”. The actions, which were standardized in this term of agreement, are actions that change the parameters of work organization and that influence LQW. The Theory of Communicative Action, developed by Habermas (2012), was used as a tool for analyzing this dialogical process, and the QWL Systemic Model, developed by Vilas Boas and Morin (2015), was used as theoretical basis for Quality of Working Life. As converging points of these theories, we verify the participation of the workers and autonomy. The research, which used the hermeneutical approach, occurred in two phases. In the first, many texts were analyzed by means of analytical categories (dialogicity, intersubjectivity, validity and legitimacy, and consensus). In the second, an opinion research was answered by the Administrative Technicians in Education regarding their perception of the dialogical process. With this research, it was possible to understand that the Life Quality at Work actions are legitimate and valid if resulting from a dialogical process with the compromise of a consensus.